Promises - Shapiro, Justine; Goldberg, B.Z.; Bolado, Carlos (United States, 2001)
Soros Documentary Fund The filmmaker travels to a Palestinian refugee camp and to an Israeli settlement in the West Bank, and to the more familiar neighborhoods of Jerusalem where he meets seven Palestinian and Israeli children. Though the children live only 20 minutes apart, they exist in completely separate worlds; the physical, historical and emotional obstacles between them run deep. The film explores the nature of these boundaries and tells the story of a few children who dared to cross the lines to meet their neighbors. Rather than focusing on political events, the seven children featured in “Promises” offer a refreshing, human and sometimes humorous portrait of the Palestinian-Israeli conflict.